2010
DOI: 10.1111/j.1468-5965.2010.02127.x
|View full text |Cite
|
Sign up to set email alerts
|

Realism and the Common Security and Defence Policy

Abstract: The European Union has ventured into the business of power politics with its common security and defence policy (CSDP). Realism can explain both why the EU is being pulled into this business and why it is failing to be powerful. Although realism has much to offer, it is not the dominant approach to the study of the EU and its foreign affairs because the EU is commonly perceived as capable of transcending power politics as we used to know it. The first purpose of this article is therefore to question the stereo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(23 citation statements)
references
References 52 publications
(44 reference statements)
0
21
0
2
Order By: Relevance
“…As conflicts tend to be pervasive, little agreement can be forged on foreign policy issues within the EU which becomes the result of the 'lowest common denominator' between the national interests of the member states (Nuttall, 2000). Moreover, scholars have observed that big EU member states engage in developing and accept EU foreign policy only when it promotes their interests or doesn't endanger them (Hyde-Price, 2008;Rynning, 2011). On the other hand, Europe's search for a meaning has driven scholars to enquire into the way in which the ontology of the Union predisposes it to behave in the international arena.…”
Section: The Eu's Global Presencementioning
confidence: 99%
“…As conflicts tend to be pervasive, little agreement can be forged on foreign policy issues within the EU which becomes the result of the 'lowest common denominator' between the national interests of the member states (Nuttall, 2000). Moreover, scholars have observed that big EU member states engage in developing and accept EU foreign policy only when it promotes their interests or doesn't endanger them (Hyde-Price, 2008;Rynning, 2011). On the other hand, Europe's search for a meaning has driven scholars to enquire into the way in which the ontology of the Union predisposes it to behave in the international arena.…”
Section: The Eu's Global Presencementioning
confidence: 99%
“…If we shift the focus to classical realism (Rose 1998;Rynning 2011) smaller states reappear as relevant objects of analysis. Moreover, the geopolitics of territory, population flows and frontiers become important (Waever 1992a: 172;Ashley 1987;Rudolph 2003).…”
Section: A Realist Explanationmentioning
confidence: 99%
“…Emphasizing both military and civilian capabilities, CSDP missions have been underway since 2003 and seek to promote regional stability. However, some skeptics have decried the rise of CSDP as a new security pillar, arguing that it undermines the importance of the North Atlantic Treaty Organization (NATO) and threatens the US-EU transatlantic security relationship through its balancing effect (Rynning, 2011). I argue that this criticism of CSDP is weak and rather a misconception.…”
Section: Introductionmentioning
confidence: 98%